Socialization Use of the Internet and Social Media to Increase Productive Activities for Small Business Actors in Bacukiki District, Pare Pare City - Retyana Wahrini; Hasbi; Ganggang Canggi Arnanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
UMKM are businesses owned by individuals. UMKM are expected to help economic growth in Indonesia. The purpose of this community service is to help UMKM, especially chicken farms, in the marketing process based on the internet and social media. The service method used is through marketing socialization using social media in the form of Instagram and Facebook. Community service activities consist of 3 stages, namely preparation and planning, implementation of activities, evaluation and monitoring. The results of this activity are that partners gain new understanding and experience in marketing products using social media. The results of the community service carried out are that partners have an understanding of using the internet as a marketing tool. Partners also have the ability to market products using social media Facebook and Instagram. As for suggestions for UMKM in chicken farms, they can consistently market through social media, and suggestions for community service providers are that continued community service programs need to be carried out so that the community, especially UMKM actors, continues to be helped.